Draft Annual Plan 1982-83 Vol II Government of Tripura - Planning Commission (Planning Commission, 1982)
The Annual Plan 1982-83 has been drawn up keeping in view the national objective of growth and employment. The schemes have been included in the Plan to increase production of all important crops in General and food production in particular. This objective is proposed to be achieved by adopting proper land use planning and water management supported by latest technology in agricultui suitable for the State. Further diversification and multiple cropping are proposed to be intensified for better economic return to the cultivator. It is also proposed to utilise the highland more efficently by introducing n ew varieties of field crops suitable for high land and also extending and introducing cultivation of plantation crops.
Government of Tripura